2018
DOI: 10.3389/fpsyg.2018.01405
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Similarly Facilitates Men and Women’s Selective Attention Task Response Times but Differentially Affects Memory Task Performance

Abstract: Previous research has found that acute, moderate-intensity physical exercise enhances selective attention and memory and that men and women show differential performance on tasks measuring these skills. Although exercise and participant sex have been examined separately, it remains unknown whether acute, moderate-intensity exercise differentially affects men and women’s selective attention and memory encoding and retrieval. Participants in the present study completed two 10-min sessions of either moderate-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 106 publications
(158 reference statements)
1
9
0
2
Order By: Relevance
“…Nevertheless, it is highly interesting that the connectivity strength within the FPN was increased by physical exercise of 'low' intensity: The superior frontal gyrus and the inferior parietal lobule showed a significant increase in rs-FC after 'low'-intensity exercise, while a significant decrease in rs-FC in the superior frontal gyrus was found after 'high'-intensity exercise. Our findings on elevated FC in networks mediating attentional control processes specifically after 'low'-intensity exercise bouts are well in line with a number of studies in the literature that have reported improved attention and cognitive performance after low to moderate exercise bouts [51][52][53]. According to several studies and meta-analysis the relationship between exercise intensity and cognitive performance is Ushaped [54][55][56][57], i.e.…”
Section: Modulation Of the Fpn After 'Low'-intensity Exercisesupporting
confidence: 90%
“…Nevertheless, it is highly interesting that the connectivity strength within the FPN was increased by physical exercise of 'low' intensity: The superior frontal gyrus and the inferior parietal lobule showed a significant increase in rs-FC after 'low'-intensity exercise, while a significant decrease in rs-FC in the superior frontal gyrus was found after 'high'-intensity exercise. Our findings on elevated FC in networks mediating attentional control processes specifically after 'low'-intensity exercise bouts are well in line with a number of studies in the literature that have reported improved attention and cognitive performance after low to moderate exercise bouts [51][52][53]. According to several studies and meta-analysis the relationship between exercise intensity and cognitive performance is Ushaped [54][55][56][57], i.e.…”
Section: Modulation Of the Fpn After 'Low'-intensity Exercisesupporting
confidence: 90%
“…Among the 6621 articles, 6569 were excluded and 52 full text articles were reviewed. Among these 52 articles, five were duplicates and 22 were ineligible [5,24,25,26,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61] as they did not provide enough data for an effect size calculation. Thus, in total, 25 articles met our inclusionary criteria and were eligible for the quantitative meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two intervention studies found sex differences. One study [8] in young individuals (mean age 19.7 years) found that two 10-min sessions of moderate intensity exercise resulted in overall faster performance on a selective attention test in both men and women. Women showed better recognition memory than men, but there was improved object location memory only among men, and only among men who completed the memory task second.…”
Section: Discussionmentioning
confidence: 99%
“…The planned analyses for our trial did not incorporate sex moderation. Few randomized controlled trials have addressed the potential moderation of exercise effects by sex despite the fact that several observational and intervention studies have found sex differences in the cognitive benefit from physical exercise or physical activity [7,8,9,10,11,12,13]. Two meta-analyses [3,14] suggested that women might benefit from aerobic exercise more than men, but these analyses were not based on direct comparison of exercise benefit by sex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation